2008
DOI: 10.1111/j.1467-940x.2008.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Interregional Income Inequality in Postwar Japan: Theil Decomposition and Gap Accounting Analyses

Abstract: This study empirically identifies some factors of interregional income inequality in postwar Japan during the period 1955–2005 using a decomposition analysis with a Theil L index and a gap accounting analysis. One major empirical finding was that interregional inequality in per capita GDP during the period 1955–2005 showed a double peaked M‐shaped curve, which was predominantly attributed to interregional inequality in labor productivity. The sectoral decomposition analysis revealed that the factors that cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Employing the coefficient ratio of private capital to employment, the distribution share of employment is plausibly about 61 %, as often observed in previous studies, such as Yamano and Ohkawara (2000) and Kataoka (2008). Moran's I (Table 1) shows lower quinquennial values, although we cannot reject the null hypothesis of no spatial autocorrelation between the error term in Model 3 and the spatial weight matrix for most sample years.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Employing the coefficient ratio of private capital to employment, the distribution share of employment is plausibly about 61 %, as often observed in previous studies, such as Yamano and Ohkawara (2000) and Kataoka (2008). Moran's I (Table 1) shows lower quinquennial values, although we cannot reject the null hypothesis of no spatial autocorrelation between the error term in Model 3 and the spatial weight matrix for most sample years.…”
Section: Resultsmentioning
confidence: 51%
“…The reverse is true for prefectures that have the lowest coefficient values, which are located far from this region, namely Kochi (0.090), Tottori (0.090), Shimane (0.091), Miyazaki (0.095), and Saga (0.096). However, the presented estimates have lower coefficient values of public capital than those of Yamano and Ohkawara (2000) and Kataoka (2008), partially because the data used herein cover the prolonged recession period and because the spillover effects variable is included in our model.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In East Asia, Japan's interregional inequality in per capita GDP during the 1955–2005 period shows a M‐shaped trajectory (Kataoka ; Saito ). Yun found that inequality within South Korea reached unprecedented levels since the early 1980s, with rising gaps in income, consumption, and education between the rich and the poor (2009).…”
Section: Changing Spatial Inequality In Asiamentioning
confidence: 99%
“…Among East Asian countries, public investment is crucial to the regional inequality of labor productivity in Japan (Kataoka ). Kim and colleagues found that income inequality in South Korea was positively correlated to the distribution of decentralization instruments, such as educational services, employment, infrastructure facilities, and information network access (2003).…”
Section: Sources and Factors Of Spatial Inequality In Asiamentioning
confidence: 99%